Uric acid sensing using tapered silica optical fiber coated with zinc oxide nanorods - Yusof, Haziezol Helmi Mohd; Rahim, Hazli Rafis Abdul; Thokchom, Siddharth; Dimyati, Kaharudin; Harun, Sulaiman Wadi (John Wiley & Sons, 2018)
In this paper, fiber-optic sensors by different tapered lengths of silica optical fiber (SOF) coated with zinc oxide (ZnO) nanorods were fabricated and demonstrated to detect different concentrations of uric acid. The SOFs were tapered in the length of 1 cm, 3 cm, 5 cm, and 7 cm using flame brushing technique. ZnO nanorods were coated on the surface of the tapered SOFs for 24 hours using sol-gel immersion method. The sensing experiment was performed by dipping the SOF in the uric acid solution. One end of the SOF was connected to a light source and while the other end to an optical analyzer. The output of the sensor was analyzed for different uric acid concentration from 0 ppm to 500 ppm with the different tapered lengths of SOF sensors. The result shows that the sensor with tapered length of 7 cm had the highest sensitivity response of 0.0006 mV/ppm with linearity of 98.52%. In addition, all tapered size of sensor shows significant improvement of sensing performance with sensitivity consistently improved from 1 cm to 7 cm with good linearity as ZnO nanorods coated the tapered lengths. The detection limit was found to be at 0.2 ppm in the range of uric acid concentration.